THE FIRST FIND OF HETEROMORPH AMMONITES IN THE LOWER CALLOVIAN OF EUROPEAN RUSSIA - Gulyaev D.B. (My University, 2002)
Middle Jurassic heteromorph ammonites Parapatoceras tuberculatum (Baugier et Sauze) have been found for the first time in the Lower Callovian koenigi Zone of European Russia (Kostroma Region, Kologrivskii District).
Keywords: Callovian; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Средний::Келловейский